The effectiveness of peace keeping operations - Di Salvatore, J; Ruggeri, A (Oxford University Press, 2017)
Peacekeeping has been one of the main conflict management tools used by the international community to restore or safeguard peace and security. Since 1948, the United Nations has established 70 peace operations and has substantially evolved, adopting approaches to peace that extend beyond purely military concerns. Indeed, the promises of peacekeeping as effective instrument of conflict reduction may, to some extent, explain the evolution toward multidimensional missions and the unprecedented number of peacekeepers deployed in the last decade. As consequence, the growing importance of peacekeeping effectiveness has sparked a new wave of research that empirically investigates whether and under which conditions UN peacekeeping works.